Diverse Large HIV-1 Non-subtype B Clusters Are Spreading Among Men Who Have Sex With Men in Spain - Delgado, Elena; Benito, Sonia; Montero, Vanessa; Cuevas, María Teresa; Fernández-García, Aurora; Sánchez-Martínez, Mónica; García-Bodas, Elena; Díez-Fuertes, Francisco; Gil, Horacio; Cañada, Javier; Carrera, Cristina; Martínez-López, Jesús; et al. (Frontiers in Microbiology, 2019)
In Western Europe, the HIV-1 epidemic among men who have sex with men (MSM) is dominated by subtype B. However, recently, other genetic forms have been reported to circulate in this population, as evidenced by their grouping in clusters predominantly comprising European individuals. Here we describe four large HIV-1 non-subtype B clusters spreading among MSM in Spain. Samples were collected in 9 regions. A pol fragment was amplified from plasma RNA or blood-extracted DNA. Phylogenetic analyses were performed via maximum likelihood, including database sequences of the same genetic forms as the identified clusters. Times and locations of the most recent common ancestors (MRCA) of clusters were estimated with a Bayesian method. Five large non-subtype B clusters associated with MSM were identified. The largest one, of F1 subtype, was reported previously. The other four were of CRF02_AG (CRF02_1; n=115) and subtypes A1 (A1_1; n=66), F1 (F1_3; n=36), and C (C_7; n=17). Most individuals belonging to them had been diagnosed of HIV-1 infection in the last ten years. Each cluster comprised viruses from 3 to 8 Spanish regions and also comprised or was related to viruses from other countries: CRF02_1 comprised a Japanese subcluster and viruses from 8 other countries from Western Europe, Asia, and South America; A1_1 comprised viruses from Portugal, UK, and USA, and was related to the A1 strain circulating in Greece, Albania and Cyprus; F1_3 was related to viruses from Romania; and C_7 comprised viruses from Portugal and was related to a virus from Mozambique. A subcluster within CRF02_1 was associated with heterosexual transmission. Near full-length genomes of each cluster were of uniform genetic form. Times of MRCAs of CRF02_1, A1_1, F1_3, and C_7 were estimated around 1986, 1989, 2013, and 1983, respectively. MRCA locations for CRF02_1 and A1_1 were uncertain (however initial expansions in Spain in Madrid and Vigo, respectively, were estimated) and were most probable in Bilbao, Spain, for F1_3 and Portugal for C_7. These results show that the HIV-1 epidemic among MSM in Spain is becoming increasingly diverse through the expansion of diverse non-subtype B clusters, comprising or related to viruses circulating in other countries.